Happinimal Project: Kampanye Kebebasan Hewan agar Sejahtera - Zayyana Khairunnisa Lubis; Banna Rosyid Madani; Rizky Satya Reswara; Tutut Chusniyah (Flourishing Journal, 2023)
The Happinimal Project program is a social-based Animal Freedom campaign that aims to maintain animal welfare. The term "Animal Welfare" itself is increasingly being used by companies, consumers, veterinarians, politicians and others. The term focuses on the animal's body and physical environment. This research examines the aspects of animals that are measured from the results of different behaviors. The implementation of this campaign is to use the author's Instagram story and the social media campaigns that have been carried out do not always go as expected because there is a decrease in the number of impressions. This is due to various other factors such as upload hours and the attractiveness of other Instastories outside of the project. However, the conclusion from the posttest results after giving the material shows an increase in percentage. The increase in the percentage of correct answers shows the effectiveness of delivering the initial material to the last material. The target community has received education regarding Animal Welfare and can remember it, this can be seen from the results of the answers that have increased in the posttest. The conclusion of this program is that the target community already knows in general about the principles of animal welfare, and the Happinimal Project program can increase the percentage of people's knowledge of animal welfare.Abstrak Program Happinimal Project adalah kampanye Animal Freedom berbasis sosial yang bertujuan untuk menjaga kesejahteraan hewan. Istilah “Kesejahteraan Hewan” sendiri, dewasa ini semakin banyak digunakan oleh perusahaan, konsumen, dokter hewan, politisi, dan lainnya. Istilah tersebut berfokus pada tubuh dan lingkungan fisik hewan. Penelitian ini mengkaji tentang aspek hewan yang diukur dari hasil perilaku yang berbeda-beda. Penerapan kampanye ini adalah menggunakan story Instagram penulis dan dalam kampanye sosial media yang telah dilakukan tidak selalu berjalan sesuai harapan karena terdapat penurunan jumlah tayangan. Hal ini dikarenakan berbagai faktor lain seperti jam upload dan daya tarik dari Instastory lain di luar projek. Namun deminikan, kesimpulan dari hasil posttest setelah pemberian materi menunjukan kenaikan persentase. Kenaikan persentase jawaban yang benar menunjukkan efektifitas dari penyampaian materi awal hingga materi terahir. Masyarakat target sudah mendapatkan edukasi terkait kesejahteraan hewan dan dapat mengingatnya, hal ini dapat dilihat dari hasil jawaban yang meningkat pada posttest. Kesimpulan dari program ini adalah masyarakat target sudah mengetahui secara umum tentang prinsip kesejahteraan pada hewan, dan dengan diadakannya program Happinimal Project dapat meningkatkan persentase pengetahuan mayarakat akan kesejahteraan hewan.